REGULATING THE PRINCIPLE OF GOOD FAITH IN INVESTOR-STATE ARBITRATION: MEANINGFUL REFORM OR REARRANGING DECKCHAIRS ON THE TITANIC? (UUM Journal of Legal Studies, 2026)
In investor-state arbitration—the principal mechanism enabling foreign investors to bring claims against host-states—the principle of good faith functions as an omnipresent force, intricately woven into the fabric of its proceedings. Its influence permeates every aspect of the field: where the sovereignty of host-states and the conduct of foreign investors are examined, tribunals frequently invoke the principle to construe parties’ obligations, with findings of good or bad faith often determining the outcomes of disputes. Despite its integral role, the principle remains susceptible to inconsistent interpretation and uncertain application, reinforcing stakeholders’ concerns regarding the urgent need for reform. This article examines the necessity of regulating the application of the principle of good faith in investor-state arbitration and explores potential reforms toward that end. Employing a doctrinal methodology, it draws upon arbitral decisions, UNCITRAL discussions, and relevant literature. The findings reveal that the urgency of regulation is most apparent in contexts involving corruption, treaty shopping, the fair and equitable treatment standard, and the allocation of costs. To address these issues, the article proposes both principle-based reforms—such as adopting a coherent definition of good faith and incorporating it explicitly into bilateral investment treaties (BITs)—and structural reforms, including the adoption of a doctrine of precedent, the establishment of an appellate mechanism, a ban on double-hatting, and the introduction of clear rules on cost allocation. Ultimately, regulating the principle of good faith is vital to ensuring greater predictability, coherence, and legitimacy within the investor-state arbitration system.
Keywords: Investor-state arbitration; principle of good faith; United Nations Commission on International Trade Law